MEMBERIKAN KENYAMANAN KONSUMEN SAAT DUDUK DI KABIN PENUMPANG PADA MOBIL TOYOTA RUSH 2009 DENGAN FITUR FOOT STAND JUGA SEBAGAI PELENGKAP DARI FITUR WHIPLASH INJURY LESSENING (WIL) CONCEPT SEAT - Agit Sakti Nur Kholis (Universitas Negeri Yogyakarta, 2020)
There are several cars with SUV type designs from the manufacturer with only 4 passenger seats with luggage, for example, one of them is the Toyota Rush 2009 and there are also those that have been designed for 7 passengers, such as the Isuzu MU-X and Daihatsu Terios. In this case it was found that several owners of SUVs with only 4 passengers, one of which was the Toyota Rush. Where the owner forced to modify the Toyota Rush from 4 passengers to 7 passengers. However, the increase in the number of seats can cause inconvenience for vehicle passengers in the rear row. Therefore, this article aims to design a foot stand on the Toyota Rush which is modified into 7 seats so that it can improve passenger comfort. The design process is carried out through the construction analysis, design, and simulation stages. The results show that the addition of a foot stand can increase comfort for passengers who sit in the back row because it has wider and more loose leg room.